Apart from judgement. (6th April 2023) - Johnson, Helen
In this text the relation between art therapy and art as such is explored, drawing on moments in the emergence of art therapy practice in a western context. The text examines differences in the role of imagination for art and art therapy, and identifies the roles of audience and conceptual rationale as points of difference between the two.